The impact of wars and asylum on modern Arabic narrative discourse (The International Journal for Scientific Research, 2025)
This research examines the impact of conflict and displacement on narrative discourse in terms of form and content, highlighting the changes that have occurred in narrative structure under forced experiences of displacement and exile. The research focuses on how fictional literature embodies human suffering, divided identity, and fragmented memory through narrative techniques that vary between fragmentation, polyphony, and the alignment of documentation and imagination. The research also demonstrates the role of war in dismantling the conventional structure of narrative text, making narrative a tool for resistance and preserving collective memory. The research traces the characteristics of this genre of literature, such as the presence of the lost homeland as a symbol, longing as a narrative motivator, and the complex relationship between self and other in exile.Accordingly, the study presents a set of findings that demonstrate how narrative literature has transformed into a cultural and historical testimony. It concludes with recommendations that encourage the support of this discourse through translation, publication, documentation, and enabling refugees to narrate their experiences in their own unique ways.
Keywords: Arabic Narrative Discourse; Arabic Language; Wars; Asylum